Living like a girl : agency, social vulnerability and welfare measures in Europe and beyond - Vogel, Maria A.; Arnell, Linda (Transnational girlhoods, 2021)
"In recent decades, large-scale social changes have taken place in Europe. Ranging from neoliberal social policies to globalization and the growth of EU, these changes have significantly affected the conditions in which girls shape their lives. Living Like a Girl explores the relationship between changing social conditions and girls' agency, with a particular focus on social services such as drug rehabilitation programs and compulsory institutional care. The contributions in this collected volume seek to expand our understanding of contemporary European girlhood by demonstrating how social problems are managed in different cultural contexts, political and social systems"--